Examining Marital Flourishing in Intercultural Couples: A Psychological Literature Review - Desyanadia Putri; Mira Ariyani; Zarina Akbar (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
Intercultural marriage has become increasingly common in the era of globalization; however, cultural differences between partners introduce complex challenges in maintaining marital well-being. This literature review aims to explore the concept of marital flourishing within the context of intercultural couples and the psychological factors that support it. Using a narrative literature review method, the study analyzed 12 relevant articles published between 2015– 2025 that focus on the psychological aspects of intercultural marriage. The findings reveal that marital flourishing is influenced by a combination of internal factors (such as self-compassion, mindfulness, and life management skills), effective communication, communal values, religiosity, and social support. Cultural differences necessitate ongoing adaptation and cultural negotiation. This study highlights the importance of a multidisciplinary approach and culturally sensitive interventions to support intercultural couples in building a healthy and fulfilling marriage.